Cardiovascular causes of maternal sudden death. Sudden Arrhythmic Death Syndrome is leading cause in UK. (September 2017) - Krexi, Dimitra; Sheppard, Mary N
Abstract: Objective: This study aims to determine the causes of sudden cardiac death during pregnancy and in the postpartum period and patients' characteristics. There are few studies in the literature. Methods: Eighty cases of sudden unexpected death due to cardiac causes in relation to pregnancy and postpartum period in a database of 4678 patients were found and examined macroscopically and microscopically. Results: The mean age was 30 ± 7 years with a range from 16 to 43 years. About 30% were 35 years old or older; 50% of deaths occurred during pregnancy and 50% during the postpartum period. About 59.18% were obese or overweight where body mass index data were available. The leading causes of death were sudden arrhythmic death syndrome (SADS) (53.75%) and cardiomyopathies (13.80%). Other causes include dissection of aorta or its branches (8.75%), congenital heart disease (2.50%) and valvular disease (3.75%). Conclusion: This study highlights sudden cardiac death in pregnancy or in the postpartum period, which is mainly due to SADS with underlying channelopathies and cardiomyopathy. We wish to raise awareness of these frequently under-recognised entities in maternal deaths and the need of cardiological screening of the family as a result of the diagnosis.